P182125 YEARS OF GROWTH HORMONE TREATMENT IN CHILDREN WITH CHRONIC KIDNEY DISEASE IN POLAND - RESULTS OF NATIONAL MULTICENTER STUDY. (6th June 2020) - Leszczyńska, Beata; Daniel, Maria; Majcher, Anna; Pyrzak, Beata; Szczepanska, Maria; Zagozdzon, Ilona; Jander, Anna; Tkaczyk, Marcin; Sikora, Przemysław; Wasilewska, Anna; Zachwieja, Katarzyna; Miklaszewska, Monika; et al.
Abstract: Background and Aims: Growth retardation is one of considerable problems in children with chronic kidney disease (CKD) with a great impact on life activity and quality of life. Recombinant human growth hormone (rhGH) treatment has been used for more than 30 years to improve growth velocity and final growth in children with CKD. In Poland rhGH therapy in children with CKD is available since 1994. The aim of the study was to assess growth velocity in all children with CKD treated with rhGH in Poland since 1994. Method: We retrospectively analyzed 321 polish children with CKD (mean age: 10.2±7.60, 210 ♂ (65%) qualified to the rhGH therapy between 1994 and 2019. Among 321 children, 180 (56.1%) were on conservative treatment (CT), 118 (36.7%) on chronic dialysis (RRT) and 23 (7.2%) after kidney transplantation (KTx). In 240 (75%) patients who were treated continuously for at least 12 months we have evaluated: growth velocity and mean annual values of selected biochemical parameters. Results: Mean height SDS at the beginning of the treatment was -2.73±1.04 SD, among children on CT -2.22±1.20, on RRT -2.9±1.11, after KTx -3.07±1.30. Mean time of rhGH treatment was 23±10.7 months. During one-year rhGH treatment mean growth velocity in 240 children was: 8.5 ± 2.7 cm (ΔSDS 0.78±1.02) and mean height SDS increased significantly (-2, 73±1.04 vs. -1.92±1.11, p<0.0001). Children on CT did not differ significantly in age vs. children on RRT (10.66±3.40 vs. 10.26±3.61 years, p =0.972), and growth velocity was slower in RRT group expressed in cm (7.52±2.59 vs. 9.2±2.30, p<0.0001) and in ΔSDS (0.4±0.83 vs. 0.72±1.15, p=0.045). Growth velocity (ΔSDS) correlated negatively with age of rhGH initiation in children on CT (r=-0.40, p=0.008) and on RRT (r=-0.28, p=0.03). We found no significant relation between growth velocity and sex, cause of CKD, hemoglobin, total protein, albumin, urea, creatinine, calcium, phosphorus, Ca x P, PTH and alkaline phosphatase. Conclusion: 1. Growth hormone treatment is highly effective in children with CKD especially those who are treated consevatively. 2. Early initiation of rhGH therapy is the crucial factor determining response to the treatment in children with CKD.